DESIGNING VIRTUAL CHARACTERS AS EDUCATIONAL CONTENT SUPPORT FOR ANANTAKA FOUNDATION - Prasetiyo, Sheehan Rizky Akbar; Prameswari, Nadia Sigi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
With the rise of digital technology, social media platforms such as Instagram and YouTube have become essential tools for disseminating educational materials, reaching a broader and younger audience. This project focuses on the design of virtual characters as a supportive tool for educational content production by the Anantaka Foundation, a non-governmental organization dedicated to social education in Semarang. Virtual YouTubers (VTubers), animated characters who interact with audiences via video platforms, represent a growing phenomenon in digital content creation. This project proposes creating a VTuber model that aligns with Anantaka's signature brand identity, aiming to enhance the foundation's outreach, especially among teenagers, by integrating anime art styles. The design process involved several stages, including brainstorming, sketching, outlining, coloring, and rendering, using digital tools such as Clip Studio Paint. The final product will serve not only as a visual mascot but also as an engaging element in Anantaka's educational content across social media platforms. By creating a virtual character, this project seeks to attract new audiences, maintain brand identity, and offer a fresh, interactive way to disseminate educational information. This innovative approach demonstrates the potential of VTubers beyond entertainment, proving their effectiveness in the fields of education and social outreach.